2016
DOI: 10.1016/j.ajog.2015.09.082
|View full text |Cite
|
Sign up to set email alerts
|

New development of the yolk sac theory in diabetic embryopathy: molecular mechanism and link to structural birth defects

Abstract: Maternal diabetes is a significant risk factor for structural birth defects, including congenital heart defects and neural tube defects (NTDs). With the rising prevalence of type 2 diabetes and obesity in women of childbearing age, diabetes-induced birth defects have become an increasingly significant public health problem. Maternal diabetes in vivo and high glucose in vitro induce yolk sac injuries by damaging the morphology of cells and altering the dynamics of organelles. The yolk sac vascular system is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 147 publications
(160 reference statements)
0
36
0
2
Order By: Relevance
“…55,56 Therefore, therapeutics that can prevent diabetes-induced birth defects are needed. Antioxidants are effective in preventing adverse pregnancy outcomes associated with maternal diabetes in animal models 810,1215,17,2022,36,37 ; however, their effects on human pregnancies are controversial. 57,58 Our previous studies revealed that a group of natural compounds with antioxidant and signaling modulating properties reduces birth defects in animal diabetic pregnancies.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…55,56 Therefore, therapeutics that can prevent diabetes-induced birth defects are needed. Antioxidants are effective in preventing adverse pregnancy outcomes associated with maternal diabetes in animal models 810,1215,17,2022,36,37 ; however, their effects on human pregnancies are controversial. 57,58 Our previous studies revealed that a group of natural compounds with antioxidant and signaling modulating properties reduces birth defects in animal diabetic pregnancies.…”
Section: Commentmentioning
confidence: 99%
“…Because oxidative stress, ER stress, and apoptosis are causal events in T1DM embryopathy, our results suggest that T1DM and T2DM may share similar molecular mechanisms to cause birth defects. Based on our work to identify possible therapeutic inhibitors of the signaling pathways involved inT1DM embryopathy, 810,1215,17,2022,33,36,37 it is possible that the same interventions could successfully reduce birth defects induced by T2DM.…”
Section: Commentmentioning
confidence: 99%
“…14 There are approximately 5 times more neural tube defects in offspring from diabetic mothers than in those from nondiabetic mothers, despite modern preconception care. 15 Studies from our group 1,5,6,1625 and others 26 have demonstrated that maternal diabetes induces cellular stress, including oxidative stress and endoplasmic reticulum stress, and that those cellular stresses cause apoptosis in the embryonic neural tissue, leading to neural tube defect formation. Recently several studies have suggested that altered DNA methylation disrupts the folate metabolic pathway and causes neural tube defects.…”
mentioning
confidence: 99%
“…Although strict glycemic control by lifestyle and pharmacological treatment can decrease the incidence of hyperglycemia-induced embryonic malformations in pregnancies affected by preexisting maternal diabetes, 13,6,7 euglycemia is difficult to achieve and maintain, and even transient exposure to high glucose could lead to abnormal embryonic development. 13,1113 Thus, diabetes-induced birth defects are significant public health problems, and there is an urgent need for new therapeutic approaches against diabetic embryopathy.…”
mentioning
confidence: 99%
“…Adipositas und erhöhten Werten des C-reaktiven Proteins gebracht werden, vor allem aber mit einem nicht diagnostizierten und unbehandelten früh einsetzenden Gestationsdiabetes mellitus (FREGDM). Im Zusammenhang mit Hyperglykämien werden Vaskulogenesestörungen ab dem Zeitpunkt der Implantation und sterile inflammatorische Veränderungen in der Plazenta als Ursache einer Präeklamp-sie in einer fortgeschrittenen Schwangerschaft diskutiert [11,20].…”
Section: » Daten Des Deutschen Ivfregisters Belegen Eine Erhöhte Aborunclassified